2019
DOI: 10.13171/mjc8319050305ng
|View full text |Cite
|
Sign up to set email alerts
|

Structural and dielectric properties of Ba0.95Bi0.05Ti1-xFexO3ceramics at x=0.0, 0.1 and 0.2 prepared by solid state method

Abstract: The Ba0.95Bi0.05Ti1-xFexO3 ceramics at (x=0.0, 0.1 and 0.2) were prepared by the solid-state reaction method. The effect of iron substitution on structural and dielectric properties of Ba0.95Bi0.05TiO3 ceramic was studied. These compounds are found to crystallize in only tetragonal phase for x = 0.0 and 0.1 and the mixture of tetragonal and hexagonal phases for x = 0.2. The dielectric properties of Ba0.95Bi0.05Ti1-xFexO3 ceramics at x=0.0, 0.1 and 0.2 of Fe -doping concentration. The dielectric measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In addition to the specifc concentration of 5 % of Bi doping, a maximum of the dielectric constant is achieved in other works [17,19]. And according to our previous published works [20][21][22], the relative dielectric permittivity εr was improved and reach a value of 37 000 in Bi substituted BTFO ceramics for x=0.60 and 0.80 of Fe content and the phase transitions present a relaxation behavior with diffuse character. In these works the structural, microstructural and dielectric properties of Fe and Bico-substituted BaTiO3 ceramic were studied.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…In addition to the specifc concentration of 5 % of Bi doping, a maximum of the dielectric constant is achieved in other works [17,19]. And according to our previous published works [20][21][22], the relative dielectric permittivity εr was improved and reach a value of 37 000 in Bi substituted BTFO ceramics for x=0.60 and 0.80 of Fe content and the phase transitions present a relaxation behavior with diffuse character. In these works the structural, microstructural and dielectric properties of Fe and Bico-substituted BaTiO3 ceramic were studied.…”
Section: Introductionmentioning
confidence: 65%
“…The Bi and Fe substituted BaTiO3ceramics for x=0.00 to 1.00 of Fe contents and 0.05 of Bi content were synthesis using the conventional solid-state method as it is reported in our previous works [20][21][22]. The samples were prepared by the following chemical equation:…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Meanwhile, Fe-doped BaTiO 3 ceramics show some inconveniences that limit its application which are the low dielectric permittivity values and high dielectric phase transitions, which were confirmed by several works [ [35] , [36] , [37] ] On the other hand, the co-substitution of BaTiO 3 with Fe 3+ and Bi 3+ ceramics opens new possibilities to improve physical properties which could be compared with BFO-BT composites properties. The effect of BT co-substituted ceramics with Bi 3+ and Fe 3+ on structural, dielectric and ferroelectric properties were recently investigated in our works [ 38 , 39 ]. And it has been reported that the substitution of Fe 3+ ions into the Ti 4+ sites enhance the dielectric permittivity of Ba 0·95 Bi 0·05 TiO 3 ceramic and tree phase transitions were reported assigned to Rhombohedral-Orthorhombic at T R-O = 150 °C, and Orthorhombic-Tetragonal at T O-T = 350 °C then Tetragonal- Cubic at T m > 350 °C.…”
Section: Introductionmentioning
confidence: 99%